Empowerment Of Rural Communities Through The Development Of " Soft Skills Soybean Tempe Making” In An Effort To Increase Family Income In Deli Serdang - Tongat; Umar Muhtar Seregar; Nurainun Hasibuan (International Journal of Community Service Implementation, 2023)
Many women in rural areas whose lives rely on their husbands ' income to work in the building environment where they live are not uncommon for a husband to support his family to wander out of town to work on building projects and private house buildings where there are people who need carpentry services.while waiting for the husband to come home, the mother helps increase her husband's income sometimes working in the fields,working in the fields only occasionally planting,cleaning the grass and harvesting. There is so much free time for women. That is according to the statement of the village head Muslim father, M.Pd in Jalan Balai Desa I Gg.Prosperous Hamlet III Village Tanjong Anom District Pancurbatu Deli Serdang before we held community service activities.Community service activities this time focused on the empowerment of rural communities through the development of soft skills soybean tempe making in an effort to increase family income in Deli Serdang. The purpose of this activity is the empowerment of women by providing skills that can increase family income.